An Accidental Special Issue. (13th July 2016) - LUDLOW, PIERS
Abstract : This was not intended to be a special issue. Instead, my task as editor was simply meant to be that of selecting an interesting selection of pieces from those articles available, or nearly ready, for publication. But upon looking at the list of possible candidates it quickly became clear that a large number dealt squarely with the history of European integration and that two others concentrated on other aspects of Europe's post-war institutional landscape. It therefore seemed to make sense to group them together.